2010
DOI: 10.1016/j.ad.2009.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Alopecia androgénica masculina y factores de riesgo cardiovascular: estudio de casos y controles

Abstract: The high frequency of metabolic syndrome and carotid atheromatous plaques in patients with androgenetic alopecia suggests cardiovascular screening should be done to enable early detection of individuals at risk and initiation of preventive treatment before cardiovascular disease becomes established.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 26 publications
3
10
0
Order By: Relevance
“…indicated that criteria for MetS were met by 57.1% of the patients with AGA compared to 14.3% of the controls. [18] Results of the current study are in conformity with these findings. However, Yi et al .…”
Section: Discussionsupporting
confidence: 90%
“…indicated that criteria for MetS were met by 57.1% of the patients with AGA compared to 14.3% of the controls. [18] Results of the current study are in conformity with these findings. However, Yi et al .…”
Section: Discussionsupporting
confidence: 90%
“…Recent meta‐analysis by Kim, et al highlighted the association between dyslipidaemia and AGA. The findings show significant increases in both total cholesterol and LDL levels, coupled to lower HDL, though the picture for HDL is less clear with some individual case studies reporting no changes or only small, non‐significant reductions in HDL . Total cholesterol and LDL levels were more consistently increased across the studies …”
Section: Associations Between Cholesterol and Hair Pathologiesmentioning
confidence: 92%
“…A number of studies have examined links between AGA and cholesterol levels, in particular focusing on cardiovascular disease risk and metabolic syndrome . Recent meta‐analysis by Kim, et al highlighted the association between dyslipidaemia and AGA.…”
Section: Associations Between Cholesterol and Hair Pathologiesmentioning
confidence: 99%
“…Recent studies suggested an association of metabolic syndrome—obesity, hyperlipidaemia, hypertension and diabetes mellitus type 2 or abnormally high fasting blood glucose—with FPHL. As mutations in the melanocortin 4 receptor gene ( MC4R ) have been identified in patients with morbid obesity, and about half of the women in our FPHL sample present with obesity, we considered MC4R as an interesting candidate gene. Furthermore, this neuropeptide receptor has been detected among others in the dermal papilla of the hair follicle .…”
Section: Heritable Factors—the Present Status Of Fphl Genetic Researchmentioning
confidence: 99%